Érasme, pédagogue du bonheur, dans les Colloques - Dunn-Lardeau, Brenda (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2006)
In 1518, Erasmus published The Colloquies (Colloquia), a lively Latin conversation primer, which acquainted European youths with a variety of subjects, including that of happiness. This article examines several of The Colloquies, but most notably the Senile Colloquium, to assess Erasmus' response to the question of the changing interrelationship of the two felicities-celestial and earthly-during the Renaissance. He asserts that personal happiness is no longer scorned upon as in the Middle Ages provided that honestas and voluptas walk hand in hand and philautia steer away for the sake of balance between individual and collective happiness. In addition, The Colloquies, which include pleasure seekers from all walks of life, exposes young readers to a moral discourse, wherein pagan and Christian models mingle, while avoiding the moralizing tone of earlier medieval morality texts. As for the Senile Colloquium, published in 1524 (while Erasmus wrote his Diatribè sive Collatio de libero arbitrio), it distinguishes true and false happiness and adapts the classical models of the conduct of life (voluptuous, active, contemplative) to a Christian society. Erasmus considers, as did Aristotle, that mankind is responsible for its happiness but makes the philosophia Christi the best way to achieve it.